Systematic Literature Review : Pengaruh Kemampuan Komunikasi Matematika Terhadap Hasil Belajar Siswa SMP - Ezi Julianto; Julianto, Ezi; Nuryadin, Nanang; Kurniati, Nani (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
Mathematical communication skills play an important role in supporting conceptual understanding and improving student learning outcomes. This article aims to examine the effect of mathematical communication skills on student learning outcomes through a literature study approach. Data were collected from 20 scientific articles discussing the relationship between mathematical communication and learning outcomes. The results of the study indicate that mathematical communication skills have a significant influence on learning outcomes, both directly and through interactions with other variables such as self-confidence, learning interest, and learning independence. Interactive learning models such as Think Pair Share, Problem Based Learning, and Think Talk Write have proven effective in improving these abilities. Therefore, the development of mathematical communication should be a priority in learning to produce reflective, critical, and communicative students.